Review on the performance of crossflow hydraulic turbine for local power generation: Fundamentals and applications - Nobuyuki Fujisawa; Tomomi Uchiyama; Shouichiro Iio (Next Energy, 2025)
This article reviews theoretical, numerical, and experimental studies on the performance of crossflow hydraulic turbine for local renewable power generation from rivers and open channels. The main advantage of crossflow hydraulic turbines is their structural simplicity and low manufacturing cost in comparison with the other types of hydraulic turbines. It is well suited for local power generation in rural areas. This article describes the improvements in the performance of open and closed types of crossflow hydraulic turbines achieved by optimizing design parameters such as the number of blades, blade shape and thickness, inlet and outlet angles, diameter ratio, and aspect ratio. The full operating range of the turbine is summarized, including the off-design conditions. Attention is focused on numerical approaches for predicting the 2-phase flow in the turbine using the volume-of-fluid method and particle method. These are applied to the prediction of the crossflow turbine performance with respect to the experimental results in the literature. Furthermore, the improved performance including the noise of the crossflow turbine using the cavity was demonstrated for the application to prototype design.